The Effect of Adding Thyme vulgaris and Cinnamomun zeylanicum on production performance and some blood traits in broiler chicken: GALIB A.M.AL-KASSIE ;YASSER J.JAMEL - AL-KASSIE, GALIB A.M. (The Iraqi Journal of Veterinary Medicine, 2009)
This experiment was carried out at poultry house, college of Veterinary Medicine, Baghdad university,Which lasted 42 days, to by adding Thymus vulgaris the used part (Leaves, Steams and Flowers) andCinnamomum zeylanicum the used part (bark) to the concentrate diet for the experimental period for 6 weeks.The study was aimed to find out the effect of thyme or cinnamon on productive, physiological blood traits ofbroilers by using 150 unsexing Arbor Acres chicks at the age of one day. These chicks were randomly dividedinto five group equally (30 chicks each). Each group was subdivided into two equal subgroup. And fed on thefollowing ration.1-The first group was fed on ordinary diet kept as a control group.2- The second group was fed on the same ration by adding 0.5% of thyme.3- The third group was fed on the same ration by adding 1% of thyme.4- The fourth group was fed on the same ration by adding 0.5% of cinnamon.5- The fifth group was fed on the same ration by adding 1% of cinnamon.The feeding period for all groups lasted 42 days, the results revealed that There is an improving inperformance traits for all treated groups compared with control group. However, the chicks fed 0.5% thymeshould better in weekly gain period feed conversion efficiency than those fed 1% thyme. In the mean time thechicks fed 1% cinnamon should significantly higher in weekly gain and fed conversion efficiency then those fed0.5% cinnamon.However, by adding thyme or cinnamon to diet cause an improving in blood traits compared with thecontrol group. The best improving in white blood cell, were obtained in the chicks fed 1% cinnamon and theyshould significantly low better stress coefficient.